Enhanced legume growth and adaptation to degraded estuarine soils using Pseudomonas sp. nodule endophytes - Flores-Duarte, Noris J.; Caballero-Delgado, Sara; Pajuelo, Eloisa; Mateos-Naranjo, Enrique; Redondo-Gómez, Susana; Navarro-Torre, Salvadora; Rodríguez-Llorente, Ignacio D. (Frontiers in Microbiology, 2022)
The joint estuary of Tinto and Odiel rivers (SW Spain) is one of the most degraded and polluted areas in the world and its recovery is mandatory. Legumes and their associated bacteria are recommended sustainable tools to fight against soils degradation and loss of fertility due to their known positive impacts on soils. The aim of this work was to isolate and characterize plant growth promoting nodule endophytes (PGPNE) from inside nodules of Medicago spp. naturally growing in the estuary of the Tinto and Odiel Rivers and to evaluate their ability to promote legume adaptation in degraded soils. The best rhizobia and non-rhizobia among 33 endophytes were selected based on their plant growth promoting properties and bacterial enzymatic activities. These strains, identified as Pseudomonas sp. N4, Pseudomonas sp. N8, Ensifer sp. N10 and Ensifer sp. N12, were used for in vitro studies using Medicago sativa plants. The effects of individual or combined inoculation on seed germination, plant growth and nodulation were studied, both on plates and pots containing nutrient-poor soils and moderately contaminated with metals/loids from the estuary. In general, inoculation with combinations of rhizobia and Pseudomonas increased plant biomass (up to 1.5-fold) and nodules number (up to 2-fold) compared to single inoculation with rhizobia, ameliorating the physiological state of the plants and helping to regulate plant stress mechanisms. The greatest benefits were observed in plants inoculated with the consortium containing the four strains. In addition, combined inoculation with Ensifer and Pseudomonas increased As and metals accumulation in plant roots, without significant differences in shoot metal accumulation. These results suggest that PGPNE are useful biotools to promote legume growth and phytostabilization potential in nutrient-poor and/or metals contaminated estuarine soils.